PENGEMBANGAN ALAT KONDENSASI PENGUKUR OKSIGEN UDARA AMBIEN UNTUK MENDUKUNG PRAKTIKUM PADA MATA KULIAH PENGETAHUAN LINGKUNGAN - Rahmat Bayu; Joko Waluyo; Mochammad Iqbal (saintifika, 2018)
At present it is using digital air measurements using much better analytical functions in the field using digital measurements that have accuracy weaknesses. Developing a condensation device into the air oxygen meter uses two methods: prioritizing Saltzman and Winkler, this corresponds to the contents in the air directly with air and oxygen. Development of atmospheric atmospheric condensation equipment for example ambient air oxygen concentration measuring generator, carried out with the R2D2 development model with a calibration process based on independent sample test Calibration T-test error test with digital titration and electrochemical methods, In addition to the significance of the measurement result is sig value 0.280 > 0, 05 and the calibration measurement results of the tool developed with a digital meter tool obtained the significance of the results that the sig value of 0.254 > 0.05 there was no difference between several samples using the method used.